Penilaian Kualitas Air Zona Tengah Sungai Batanghari Jambi - Lailal Gusri; Siti Umi Kalsum; Ratna Juwita (Jurnal Daur Lingkungan, 2022)
Good, clean, healthy and safe water quality is very important for the survival of humans and living creatures on earth. The application of the water quality index (WQI) method at a certain location and time can provide an assessment of water quality. This study took samples of water in the middle zone of Jambi Province which is at the Regencies: Tebo, Bungo, Sarolangun and Batanghari in order to test the water quality using Potential Hydrogen (pH), temperature, Dissolved oxygen (DO), Biological Oxygen Demand (BOD), turbidity, total phosphorus, nitrate nitrogen, E.coli and fecal coliforms as parameters. The purpose of the study was to identify river water pollutants level and to assess the ranking of the water quality index based on the application of the water quality index (WQI) method and the calculation of the CCME water quality index. The results of the test based on the water quality index method using the water quality index calculator for Tebo regency and Batanghari regency at rank 3 or moderate with the index is 53.72 and 53.28 respectively, while Bungo regency and Sarolangun regency are in rank 4 or bad with the index is 46.78 and 43.52, respectively. The overall water quality assessment for the middle zone is ranked 4 which is bad and the index is 49.77. While the calculation of the CCME water quality index shows the overall water quality of the middle zone is ranked 3, which is moderate and the index is 71.1.